Safety and Efficacy of Turoctocog Alfa in the Prevention and Treatment of Bleeding Episodes in Previously Treated Patients from China with Severe Hemophilia A: Results from the Guardian 7 Trial - Wu R; Sun J; Xu W; Hu Q; Li W; Xiao J; Yang F; Zeng X; Zeng Y; Zhou J; Matytsina I; Zhang S; et al. (Dove Medical Press, 2020)
Runhui Wu,1 Jing Sun,2 Weiqun Xu,3 Qun Hu,4 Wenqian Li,5 Jianwen Xiao,6 Feng’e Yang,7 Xiaojing Zeng,8 Yun Zeng,9 Jianfeng Zhou,4 Irina Matytsina,10 Sali Zhang,11 Michael Pluta,12 Renchi Yang13 1Hematology Oncology Center, Beijing Children’s Hospital, Capital Medical University, National Children’s Health Center, Beijing, People’s Republic of China; 2Department of Hematology, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 3Department of Hematology and Oncology, The Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, People’s Republic of China; 4Department of Pediatric Hematology, Tongji Hospital, Tongji Medical College of HUST, Wuhan, People’s Republic of China; 5Department of Hematology and Rheumatology, Qinghai Provincial People’s Hospital, Xining, People’s Republic of China; 6Department of Hematology, Children’s Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 7Department of Hematology, Fujian Medical University Union Hospital, Fuzhou, People’s Republic of China; 8Department of Blood Transfusion, The Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of China; 9Department of Hematology, First Affiliated Hospital of Kunming Medical University, Kunming, People’s Republic of China; 10Biopharm Medical & Science, Novo Nordisk A/S, Søborg, Denmark; 11Biopharm Clinical, Medical and Regulatory Affairs, Novo Nordisk (China) Pharmaceuticals Co., Ltd, Beijing, People’s Republic of China; 12Statistical Consultancy, Quanticate Ltd, Hitchin, UK; 13Thrombosis and Haemostasis Centre, State Key Laboratory of Experimental Hematology, Tianjin Laboratory of Blood Disease Gene Therapy, CAMS Key Laboratory of Gene Therapy for Blood Diseases, National Clinical Research Center for Hematological Disorders, Institute of Hematology and Blood Diseases Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Renchi YangThrombosis and Haemostasis Centre, State Key Laboratory of Experimental Hematology, Tianjin Laboratory of Blood Disease Gene Therapy, CAMS Key Laboratory of Gene Therapy for Blood Diseases, National Clinical Research Center for Hematological Disorders Institute of Hematology and Blood Diseases Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of ChinaTel +86 13512078851Email rcyang65@163.comPurpose: Hemophilia care in China is characterized by widespread use of on-demand regimens and low-dose prophylaxis. With a limited number of approved recombinant factor VIII (FVIII) products, the incidence of arthropathy and disability in hemophilia patients remains high in China. The purpose of this trial was to evaluate the safety and efficacy of turoctocog alfa for prophylaxis and treatment of bleeding episodes in patients from China with severe hemophilia A across all age groups.Patients and Methods: In this Phase 3, open-label trial, previously treated males of all ages with severe hemophilia A from China received turoctocog alfa for prophylaxis or on-demand treatment of bleeds. The primary endpoint was hemostatic effect for the treatment of bleeds during the main phase of the trial. Secondary endpoints included annualized bleeding rate during prophylaxis and the frequency of FVIII inhibitor development.Results: Overall, 42 pediatric patients (age < 12 years) and 26 adolescent/adult patients (≥ 12 years) were dosed with turoctocog alfa; 51 patients initiated treatment with prophylaxis, while 17 patients initiated on-demand treatment. During the main phase of the trial (6 months), hemostatic success was 95.1%. During the full trial (up to 24 months), hemostatic success was 95.4%; the overall median ABR was 1.18 bleeds/patient/year for prophylaxis patients; and 25 (51.0%) of 49 patients with target joints at baseline had all target joints resolved. No FVIII inhibitors (≥ 0.6 BU) were reported.Conclusion: Turoctocog alfa was safe and effective for prophylaxis and treatment of bleeding episodes and for surgery in patients from China with severe hemophilia A across all ages.Keywords: hemophilia A, prophylaxis, recombinant factor VIII, turoctocog alfa, China